Pre-processing and Classification of Prostate Images for Cancer Detection: A Survey - PC, Swetha; Kabadi, Mohan G; Srivinay, Srivinay (International Journal of Computer Sciences and Engineering, 2025)
In the recent years, prostate cancer has become the major cause of deaths in the male population around the world. Numerous computer aided techniques such as, Computer Aided Diagnosis (CAD) systems have been designed in order to detect prostate cancer. The CAD systems majorly consist of four stages namely preprocessing, segmentation, feature extraction and finally the classification stages that are interdependent on one another. The CAD systems perform the analysis based on the various screening techniques such as X-Ray, CT scans, TRUS images, MRI scan, and mp-MRI scans. Though the existing CAD systems are considered feasible, the major research challenge is in improving the accuracy, specificity, speed and usability of the existing CAD systems. This paper presents a survey on the various methodologies used for detecting the prostate carcinoma using various types of screening images.